Innovative Illustration Design for the Cultural Content and Emotional Elements of Sichuan Opera Arts for China’s Gen Z - Mingyue, Duan; Chiang, Wong Shaw (Harmonia: Journal of Arts Research and Education, 2024)
With society rapidly evolving alongside digital technology and pan-entertainment, there is a notable decline in appreciation and understanding of Sichuan Opera among China’s Generation Z (Gen Z). This study aims to develop and evaluate the potential of innovative illustration as a tool to promote the cultural content and emotional elements of Sichuan Opera arts among China’s Gen Z. This qualitative participatory action-based research was guided by an iterative cycle of planning, acting, observing, and reflecting. This study comprised three stages. In the pre-design stage, nine (9) experts were selected through purposive and snowball sampling to explore their views on the cultural content and emotional elements of Sichuan Opera arts. Thematic analysis with NVivo 12 yielded six (6) cultural content, i.e., a form of expression, performance occasions, performance techniques and dance movements, performance repertoire, character roles, costumes and make-up. The emotional elements encompassed the emotions expressed within Sichuan Opera itself (such as the characters’ roles and personalities and traditional morals and philosophies), as well as people’s emotions towards Sichuan Opera (including their yearning for its sentiment and their awareness of the need to protect traditional culture). These content and elements were visually expressed through three (3) innovative illustrations in the design stage. In the post-design stage, a sample of 25 China’s Gen Z from Chengdu was conveniently selected to evaluate the effectiveness of the illustrations. The use of innovative illustrations as a medium to promote the dissemination of the art of Sichuan Opera among China’s Gen Z has successfully merged traditional culture with modern aesthetics.